The Rule of the Entrepreneurship in Social Change : Research in Social Anthropology - Hreeb, Karrar (Al-Adab Journal, 2023)
Social processes as a model of interaction tend towards standardization over time. Thus, temporal change and continuity are constant and fundamental features of the human condition. From this perspective, the typical use of the concept of change) applied only when the normal situation changes radically and rapidly ( involves several troubling claims, including the idea that stagnation is natural and that only change needs to be explained. In fact, the alternative is to think of our main topics, including society, culture, and nature, as a process that unfolds over time, and to show the changes that have occurred in them. Social anthropologists have always understood any human activity as closely linked to all other aspects of human existence (and vice versa). If we want to understand social change, we need concepts that allow us to monitor and describe change events. Entrepreneurship is one of the most important concepts that plays a major role in explaining the dynamics of societies, as it is the primary material for understanding these processes. The argument in this paper is that the concept of entrepreneurship is universal and the term should not be reduced to the common concept of business and legal creation. The dynamic nature of a society, or tendency to change, is often observed in the proliferation of entrepreneurs. The research seeks to understand and understand entrepreneurship and its role in bringing about processes of social change, by presenting multiple cultural perspectives on the concept, while maintaining a certain degree of clarity and precision in what the concept means... and showing the ways in which, the entrepreneur creates activities and practices that give new dynamic values to societies on the planet. Its different cultures.